The rhetorical strategies to create incremental innovation in applied linguistics research articles - Warsidi; Adnan, Zifirdaus (JOALL (Journal of Applied Linguistics and Literature), 2024)
Rhetorical studies within research articles have received a growing concern among linguists worldwide. However, studies on this significant area to create incremental innovation are rarely found. Understanding this need has attracted the authors to conduct the present study by investigating rhetorical strategies authors use to create incremental innovation in their research articles and analyzing linguistic features used to create innovation for their current research. In an attempt to address these purposes, the present study analyzed 37 research article introductions (RAIs) from the disciplines of Applied Linguistics published in four reputable international journals (Q1) with the Scimago Journal Ranks (SJR) higher than 0,61. This study employed a newly designed framework and linguistic feature approaches from previous studies for the analysis. The results showed three rhetorical strategies to create incremental innovation in research articles. However, of these three, most authors tend to employ Strategy 2, Presenting the existing knowledge – and then – improving it in the present study, more than the other two strategies. Then, to realize incremental innovation, they employed six linguistic features, but of these six, two features (connective adverbs and phrases denoting examining a particular issue) appeared to be the most dominant in the present data.